Study for the installation of a manufacturing plant for carbonated energy drinks made of black maca, coca leaf and blueberry - Agramonte-Mendiola, Diego Armando (2016)
The present article exhibits the results of a study that seeks to evaluate the viability of installing a carbonated energy drink plant made from black maca, coca leaves and blueberries, wich will supply the consumer with a sustained energy feed to combat physical and mental exhaustion. This product represents a healthy alternative to the stimulating beverages currently on the market. Market and engineering studies will be developed, as well as fi nancial and social evaluations, concluding that the project is viable.